The Antioxidant Activity of Yogurt Drink by Mangosteen Rind Extract (Garcinia mangostana L.) - Jeki Mediantari Wahyu Wibawanti; Zulfanita Zulfanita; Dedi Runanto (Journal of Applied Food Technology, 2019)
Yogurt drink can be produces from goat milk. Yogurt drink was added mangosteen rind extract to increase quality of product. This study aimed to determine antioxidant activity (total phenol compound, antioxidant activity by IC50 and thiobarbituric acid or TBA value) of yogurt drink from goat milk by mangosteen rind extract. Complete randomized design was used in this research with 4 treatments and 5 replications. The antioxidant activities of yogurt supplemented with 0, 1, 2, and 3% (v/v) mangosteen rind extract was analysed. The result shows that the total phenol content increased along the increase in the levels of mangosteen. Yogurt drink with mangosteen had radical higher scavenging activity than control. TBA value showed significant differences (p<0.05) among treatments. As conclusion, mangosteen rind extract had the potential to improve antioxidant and hinder the rancidity in yogurt drink.